Validation of a Scale of Post-traumatic Stress Traits in the Mexican Youth Exposed to Social Violence - Sarah Margarita, Chávez Valdez; Esparza Del Villar, Oscar Armando; Rios Velasco Moreno, Leticia Guadalupe (2020)
There is a high incidence of post-traumatic stress symptoms found in youth groups that live in areas that suffer contextual violence. The validated scale, “scale of post-traumatic stress traits in youths exposed to social violence”, summarizes the individual symptomatic incidence, helping researchers and decision makers, interested in applied areas, to perform strategies for this particular population strata. The purpose of this study was to validate a post-traumatic stress disorder (PTSD) scale from Colombia that has been used in people from cities with social violence, in two Mexican cities with the same problem of social violence. The sample included 792 participants, from the Mexican state of Chihuahua (Juarez and Chihuahua), with a mean age of 18.94 (SD = 1.51) years, aged 17 to 21. The sample was divided randomly into two subsamples to perform an exploratory factor analysis (EFA; n = 396), and a confirmatory factor analysis (CFA; n = 396). No statistically significant differences were found between both samples in socio-demographic variables. The scale had excellent internal reliability values. The items grouped in to five factors in the EFA, which were corroborated in the CFA, with acceptable factor loadings in both analyses. This PTSD scale has been validated using a Mexican sample and can be used to measure PTSD symptoms for research of clinical purposes in a Mexican population.